How does knowledge sharing and employee engagement mediate transformational leadership on creative performance - Rifai, Arif; Dalimunthe, Ritha F.; Lumbanraja, Prihatin; Absah, Yeni (Edelweiss Applied Science and Technology, 2025)
Employee creative performance is very important and urgent in driving innovation, increasing productivity, and maintaining a competitive advantage in building global competitiveness, which is becoming increasingly complex nowadays. The Resource-Based View (RBV) theory is considered one of the alternatives for building Employee Creative Performance. The RBV theory considers the ability of the company’s human resources to create competitive advantages, among which the focus of this research is on Transformational Leadership, Knowledge Sharing, and Employee Engagement towards Employee Creative Performance. Employees of the Directorate General of Sea Transportation, Ministry of Transportation of the Republic of Indonesia participated in data collection. Two hundred twenty-four fully completed questionnaires were returned via the Google Form application on WhatsApp. Next, the collected data were analyzed using the PLS-SEM method. The analysis results show that transformational leadership has a significantly positive impact on employee creative performance, both directly and mediated by knowledge sharing and employee engagement. The findings of this study offer a model of employee creative performance based on the structured relationship of transformational leadership, knowledge sharing, and employee engagement.